КРИВИЧНА ДЕЛА ПРОТИВ БЕЗБЕДНОСТИ ДРУМСКОГ САОБРАЋАЈА- КРИТИЧКИ ОСВРТ КРОЗ АНАЛИЗУ СУДСКЕ ПРАКСЕ (Heritage, 2023)
Criminal offenses against road traffic safety are included in Chapter XXVI of the Criminal Code of the Republic of Serbia under the heading Criminal offenses against public traffic safety. This paper consists of an analysis of criminal offenses against road traffic safety, as follows: Endangering public traffic Art. 289. CC, Endangering traffic by dangerous action and dangerous means, Art. 290. CC, Negligent exercise of supervision over public traffic, Art. 295. CC and Failure to provide assistance to a person injured in a traffic accident, Art. 296. CC and it is all performed through a theoretical approach and analysis of court practice.In the introduction, we pointed out the methodology of research and analysis of traffic accidents and their consequences. The second part of the paper refers to the theoretical approach, the analysis of criminal offenses against road traffic safety in the criminal legislation of the Republic of Serbia.The third part, the empirical part, includes three levels of research over a seven-year period. The first empirical part refers to reports, lawsuits and convictions for criminal offenses against road traffic safety in the territory of the Republic of Serbia,in a seven-year period (from 2015 to 2021). The results of the research performed in this part of this paper indicate extremely mild sentences imposed on the perpetrators of crimes against road traffic safety, among which suspended sentences dominate, while mild prison sentences were imposed in only 7,87% of cases.The second empirical part includes the analysis of traffic accidents and their consequences in relation to dead persons, lightly and seriously injured persons, as well as other traffic accidents that resulted only in material damage in a seven-year period (from 2015 to 2021). The purpose of this part of the research is important for monitoring the dynamics of the volume and movement of both traffic accidents and their consequences. Participants in traffic accidents, that is, drivers, passengers, pedestrians, cyclists, trucks, buses, were the subject of the third part of the research.This part of the research shows that drivers and passengers in passenger vehicles are the most vulnerable category, considering that among them are the most people killed in traffic accidents. In the concluding remarks, as a result of the research and analysis of traffic accidents and their consequences, we pointed out the necessary amendments and changes of the de lege ferenda incriminations of criminal acts against road traffic safety in the Criminal Code of the Republic of Serbia.
Keywords: criminal acts, road traffic, endangerment, negligent supervision, traffic accidents, consequences, failure to provide assistance, penal policy, judicial practice